Comprarison between the arrival direction of auroral hiss and the location of aurora observed at Syowa Station - Nishino, Masanori; Tanaka, Yoshihito; Iwai, Akira; Kamada, Tetsuo; Hirasawa, Takeo (1982)
P(論文) From the results of the simultaneous observations of direction finding of 5-8kHz auroral hiss with aurora at Syowa Station (geomagnetic latitude, -70.4°), the comparison between the exit region of auroral hiss from the ionosphere and the location of aurora has been made. The relation between the exit region of auroral hiss and 8kHz hiss intensities at Syowa and at Mizuho (geomagnetic latitude, -72.3°) Stations has been investigated. The exit regions of the narrow-band hiss emissions (≲20kHz) which usually occur at geomagnetically quiet times are located at lower latitudes than the location of aurora appearing over or to the geomagnetic south of Mizuho. In this case, the intensities of 8kHz hiss at Syowa and at Mizuho depend on the propagation distances from the exit region to the two stations. The exit regions of the wide-band hiss emissions (≲100kHz) which usually occur during geomagnetically moderate disturbances are located in a localized active region of aurora or at higher latitudes than the location of aurora appearing around the zenith or to the geomagnetic north of Syowa. In this case, the intensity of 8kHz hiss at Mizuho is highter than that at Syowa. In order to interprete these observational results, two propagation models have been proposed as regards to auroral hiss emissions which exit through the ionosphere at lower latitudes as well as at higher latitudes than the location of aurora. departmental bulletin paper